PERLINDUNGAN HUKUM KORBAN KEKERASAN SEKSUAL DIHUBUNGKAN DENGAN PENYELESAIAN RESTORATIVE JUSTICE - Nadia Nuralifia; Dwini Pradifta Azahra; Abie Pramana; Salsabila Nurul Syifa (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Sexual violence is increasingly dangerous in Indonesia. The significant increase in cases of violence in Indonesia makes sexual violence even more dangerous. Every year sexual violence is increasing. Cases of sexual violence in 2018 were 5,280 cases, while sexual violence in 2019 was 4,898 cases, and sexual violence in 2021 was 10,247 cases. The law in Indonesia is not fully able to provide the right punishment for the perpetrators. As a result of this, sexual violence is increasingly rampant and of course has an impact on the victim. Restorative justice is a substitution in the settlement of criminal acts. The application of this Restorative Justice can reduce the intensity in correctional institutions. Therefore, maximizing the resolution of cases by means of mediation aimed at improving the moral bonds that exist in society. Whether Restorative justice can protect victims and guarantee the rights of victims is why this principle is still in question for its validity. Physical and material losses seem to be easy to heal in a short period of time, but from a psychological point of view it takes a very long time, even a lifetime. Therefore, the purpose of this study is how legal protection for victims of sexual violence is related to the completion of Restorative Justice. This study uses a normative juridical method with a statutory approach and a conceptual approach. The conclusion of this study proves that Restorative Justice is not appropriate for the settlement of criminal cases of sexual violence and also cannot protect the legal rights of victims of sexual violence, because we do not know whether the perpetrator will repeat the crime of sexual violence or not.